Numerical methods for engineers - Chapra, Steven C.; Canale, Raymond P. (New York, NY : McGraw Hill Education, 2015)
The seventh edition of Chapra and Canale's Numerical Methods for Engineers retains the instructional techniques that have made the text so successful. Numerous new or revised problems are drawn from actual engineering practice. The expanded breadth of engineering disciplines covered is especially evident in these exercises, which now cover such areas as biotechnology and biomedical engineering. Excellent new examples and case studies span all areas of engineering giving students a broad exposure to various fields in engineering.
Part 1 -- Modeling, Computers, and Error Analysis -- 1) Mathematical Modeling and Engineering Problem Solving -- 2) Programming and Software -- 3) Approximations and Round-Off Errors -- 4) Truncation Errors and the Taylor Series -- Part 2 -- Roots of Equations -- 5) Bracketing Methods -- 6) Open Methods -- 7) Roots of Polynomials -- 8) Case Studies: Roots of Equations -- Part 3 -- Linear Algebraic Equations -- 9) Gauss Elimination -- 10) LU Decomposition and Matrix Inversion -- 11) Special Matrices and Gauss-Seidel -- 12) Case Studies: Linear Algebraic Equations -- Part 4 -- Optimization -- 13) One-Dimensional Unconstrained Optimization -- 14) Multidimensional Unconstrained Optimization -- 15) Constrained Optimization -- 16) Case Studies: Optimization -- Part 5 -- Curve Fitting -- 17) Least-Squares Regression -- 18) Interpolation -- 19) Fourier Approximation -- 20) Case Studies: Curve Fitting -- Part 6 -- Numerical Differentiation and Integration -- 21) Newton-Cotes Integration Formulas -- 22) Integration of Equations -- 23) Numerical Differentiation -- 24) Case Studies: Numerical Integration and Differentiation -- Part 7 -- Ordinary Differential Equations -- 25) Runge-Kutta Methods -- 26) Stiffness and Multistep Methods -- 27) Boundary-Value and Eigenvalue Problems -- 28) Case Studies: Ordinary Differential Equations -- Part 8 -- Partial Differential Equations -- 29) Finite Difference: Elliptic Equations -- 30) Finite Difference: Parabolic Equations -- 31) Finite-Element Method -- 32) Case Studies: Partial Differential Equations -- Appendix A -- The Fourier Series -- Appendix B -- Getting Started with Matlab -- Appendix C -- Getting Started with Mathcad -- Bibliography -- Index.
Includes bibliographical references (pages 954-956) and index.
Keywords: ENGINEERING MATHEMATICS -- DATA PROCESSING